Theme genre study of the Armenian-Kipchak written heritage - Меirambekova, Л.К.; Zhiembai, Б.С. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2021)
Everyone knows that rich heritage of Kipchaks, who created the state of DeshtiKipchak in Eurasia in the Middle Ages and contributed to world civilization and culture, was written in different alphabets at different times. The heritage written in the Armenian script in the Kypchak language is based on religion, literature, history, law, philosophy, natural sciences and covers the political, economic, historical and cultural spheres of life. The Armenian-Kipchak’s heritage, which has been the subject of comprehensive research by scientists since the twentieth century, is published in foreign publications, transcribed, supplemented by dictionaries and translations, and its secrets are revealed day after day. The «Armenian-Kipchak» term was introduced into science, and the life and cultural ties of medieval Kipchaks and Armenians became the basis of their research. Today there is a need for a deeper study of historical, cultural, and linguistic features of Armenian-Kipchak’s heritage, written in such a large-scale genre. The article considers a thematic and genre study of Armenian-Kipchak’s inscriptions based on the works of foreign and domestic scientists